Competitive Strategy Formulation in The Furniture Industry - Hannika Fasya; Sufrin Hannan; Yudha Heryawan Asnawi (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Since its establishment in 2021, PT XYZ has continuously experienced a decline in sales of its flagship product, the sofa furniture. Therefore, an effective strategy is needed to continue to survive and compete in the current declining sales and increase the company turnover.Purpose: The purpose of this study is to finding the right competitive strategies that can implemented by PT XYZ to keep their existence in furniture industry.Design/Methodology/Approach: This study employs a qualitative method with informant selection through purposive sampling technique. Data collection techniques include observation, and interviews. Finding/Result: The findings of this study show that to solve the decline in sales of sofa furniture, PT XYZ can implement of appropriate competitive strategies in the form of market penetration strategy (optimizing networking and digital marketing for marketing and sales) and product development (conducting research and development to foster product innovation and improving the quality of sofa products and services without neglecting the quality of products and services that are currently provided) to increase the company turnover. Conclusion: This study shows that the priority strategy to solve the decline in sales of sofa furniture, and to increase the company turnover are with market penetration and product development. Originality/Value (State of the art): This study attempts to explain the effective competitive strategies for sustaining presence in the sofa furniture industry. It is hoped that the development of the identification of competitive factors within the CPM Matrix will contribute to a more comprehensive body of literature and provide a more precise analysis of competitors. Keywords: competitive strategies, market penetration, product development, sofa furniture, CPM